Cultura efêmera: o formato Stories do Instagram no contexto dos centros culturais - Demuner, Tamara (2019)
What are the cultural centers and what they represent in the big cities and for contemporary society is the starting of this dissertation. The universe of possibilities of conceptualization of the so-called centers of culture is vast, so that there is no single, predetermined model to describe it. The physical/architectural characteristic is one of the elements that translate what this apparatus is. The difficulty of conceptualization is in the characteristics of what type of activities and functions these spaces offer to their attending public. These places, which are demarcated physically, have educational, cultural and inspirational activities and offer recreation, socialization and sports activities. Technology and digital social networks open a path to the promotion of cultural activities designed specifically for the digital environment. This opportunity should be treated as a priority to meet the repressed demand for cultural action, not just as an alternative. The Instagram Stories was shown as a platform for the use of cultural centers to disseminate its programmatic grids and the present research proposes to analyze the behavior of these institutions in the ephemeral digital platform of Instagram and its narratives to expand its contents presented in the physical/architectural spaces in order to reach the publics present in the networks